The right to mental health during the COVID-19 pandemic - Grigutytė, Neringa; Levickaitė, Karilė; Grigaitė, Ugnė (Psichologija, 2021)
The relationship between mental health and human rights is integral and interdependent. There are clinical, social and economic reasons, as well as moral and legal obligations to advance mental health care as fundamental to human rights. Significant considerations for this matter are especially crucial when addressing the COVID-19 pandemic across the world. The aim of this research study was to analyse the responses to the ongoing pandemic, concerning the human rights of persons with psychosocial disabilities and the right to the mental health of the general population, in Lithuania. Methods included online surveys, semi-structured interviews, and a focus group. This article presents the results as a complex picture containing lived experiences of mental health difficulties of the general population, barriers to accessing the needed support and services, as well as analysis of violations of human rights. It also highlights the need for more research on the long-term consequences of the pandemic and lockdowns on the mental health of the population; also, on how human rights of persons with mental health conditions, and especially those with psychosocial disabilities, can be better ensured and protected in Lithuania.